Major factors controlling late Pleistocene to Holocene soil development in the Vesuvius area (southern Italy). (29th May 2014) - Scarciglia, F.; Zumpano, V.; Sulpizio, R.; Terribile, F.; Pulice, I.; La Russa, M. F.
Summary In this paper the role of time and late Pleistocene to middle Holocene climate changes in the Somma‐Vesuvius volcano foothill (southern Italy) is investigated with a multidisciplinary approach. Four volcanic soils inter‐layered between five well‐known and well‐dated primary tephra layers were characterized. Chronological constraints were provided by the pyroclastic layers identified in the field (Pomici di Base, Pomici Verdoline, Agnano Pomici Principali, Mercato and Avellino), ranging between 22 and 3.8 thousand years (ka) before present (BP). These represent products of explosive eruptions of Somma‐Vesuvius and the Phlegrean Fields. Another pyroclastic layer (Agnano Monte Spina) from the Phlegrean Fields was also identified, and other ash layers previously unknown in the Somma‐Vesuvius stratigraphy. These were characterized with SEM‐EDS analyses, and correlated with other eruptions from the Phlegrean Fields (Soccavo 4‐5 and Tufi Biancastri) around 12 and 21 ka BP, respectively, thus resulting in further time constraints for phases of soil development. A detailed characterization of the four pedons integrated morphological, physical, chemical, mineralogical and micromorphological analyses. Soil features were interpreted in terms of dominant genetic processes and environmental conditions. The extent of soil development, assessed with pedogenetic indices and the degree of weathering of primary pumices, was only in part consistent with time‐spans of soil formation, suggesting a more important role of climate than soil age. The different extents of expression of andic properties, pumice weathering and varying clay mineralogy allowed us to relate changes to the main climatic phases that occurred during the late Pleistocene to the mid Holocene.